Charlie Joe Jackson's guide to not growing up - Greenwald, Tom, 1962- (Greenwald, Tom, 1962- Charlie Joe Jackson book ;, 2016)
"As graduation day approaches, Charlie Joe is starting to realize being a kid isn't so bad after all"--